If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -1 = 2x + -4 Reorder the terms: -1 + 7x = 2x + -4 Reorder the terms: -1 + 7x = -4 + 2x Solving -1 + 7x = -4 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -1 + 7x + -2x = -4 + 2x + -2x Combine like terms: 7x + -2x = 5x -1 + 5x = -4 + 2x + -2x Combine like terms: 2x + -2x = 0 -1 + 5x = -4 + 0 -1 + 5x = -4 Add '1' to each side of the equation. -1 + 1 + 5x = -4 + 1 Combine like terms: -1 + 1 = 0 0 + 5x = -4 + 1 5x = -4 + 1 Combine like terms: -4 + 1 = -3 5x = -3 Divide each side by '5'. x = -0.6 Simplifying x = -0.6
| 13t-4(2t-5)=15 | | 16y^3-4y^2-2y=0 | | 2n-6*4=5 | | (3x-7)-5=12 | | 22x=35 | | 12x=37 | | 18x-32=28x/2 | | 1w+2w=24 | | -1a=9 | | 7x+4x=8 | | 7x+7-6x=6 | | 7(x-3)-2x= | | y^3-12y^2+32=0 | | -6(m+1)-2c=24 | | 2x^6-x^4-2x^2+4=0 | | 1.14x=1.25 | | x^2+4=x+4 | | 0.25x=0.275 | | -9+16x=5x+13 | | (2x-9)+3x=16 | | 30-(-2)(4-x)= | | X+19+2x=-18-2x-23 | | 4(-0.142+-0.285y)=-13 | | (x-17.5)*9.5=8.085 | | 30-(2)(4-x)= | | 13.61=142.56x^6-635.47x^5+1196.7x^4-1235.9x^3+752.4x^2-261.81x+43.991 | | (x-17.5)*9.5=1.415 | | ifx+6=3thenx | | -3.3a=-33 | | X+17+2x=-22-2x-26 | | 8.6b=103.2 | | -6.9c=41.4 |